Thematic Analysis of Factors Influencing Helmet Non-Use among Motorcyclists in Gorgan - Vajihe Jalaeian Bakhshande; Seyes Rasoul Davoodi (جامعه شناسی کاربردی)
Introduction In today's world, urban expansion and evolving lifestyles have accelerated the pace of life, making efficiency increasingly important. With population growth and these changes, the use of motorcycles has surged, particularly in the northern provinces of the country, including Golestan Province. This rise can be attributed to the compact size of motorcycles and their affordability, lower fuel consumption, and ease of navigation through traffic. However, this growth in motorcycle usage has not always been matched by adequate social and cultural infrastructure, leading to issues reflected in traffic behavior. The popularity of motorcycles, especially among young people, underscores the critical importance of safety when riding. This study aimed to explore the social and cultural factors contributing to the reluctance to wear helmets. Understanding these aspects is essential for developing effective policies and interventions to enhance safety and compliance.